Neuroimaging in Psychiatric Disorders: A Bibliometric Analysis of the 100 Most Highly Cited Articles. Issue 1 (11th October 2018) - Gong, Bo; Naveed, Sadiq; Hafeez, Dawood M.; Afzal, Khalid I.; Majeed, Salman; Abele, Jonathan; Nicolaou, Savvas; Khosa, Faisal
ABSTRACT: BACKGROUND AND PURPOSE: Extensive research has been conducted to find neuroimaging biomarkers for psychiatric disorders. This study aimed at identifying trends of the 100 most highly cited articles on neuroimaging in primary psychiatric disorders. METHODS: The most highly cited original research articles were identified and analyzed, following searches of MEDLINE and Web of Science All Databases. RESULTS: The top 100 articles ranked by yearly citation (from 137.5 to 31.1) were published between 1989 and 2017. Depressive disorders (30 articles), schizophrenia spectrum and other psychotic disorders (27), autism spectrum disorder (17), substance‐related and addictive disorders (7), and post‐traumatic stress disorder (7) were among the most studied conditions. Functional magnetic resonance imaging (42), structural magnetic resonance imaging (30), and positron emission tomography (22) were the most utilized neuroimaging modalities. While 85 articles investigated the pathophysiology of psychiatric disorders (including 7 focusing on developmental changes and 1 on genetic susceptibility), 15 articles studied the impact of treatment, including antidepressants (6), deep brain stimulation (4), antipsychotics (3), behavior therapy (3), and exercise (1). The analysis also identified the most contributing authors, countries (the United States: 71 articles, the United Kingdom: 8, Canada: 5, and China: 5), and journals ( JAMA Psychiatry : 20 articles and Biological Psychiatry : 17). Ninety‐eight studies were prospective, and two were retrospective. The sample size ranged from 3 to 1, 188 (median: 21). CONCLUSIONS: Our study identified intellectual milestones in the utility of neuroimaging in investigating primary psychiatric disorders. The historic trends could help guide future research in this field.